The role of marketing communication in the distribution of petroleum products in Ghana - Sualihu, Mesuna (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Business Administration, 2009